Ten-words recall test: an effective tool to differentiate mild cognitive impairment from subjective cognitive decline - Ren, Hua; Feng, Qiansen; Chen, Lei; Li, Linlin; Wang, Jiayu; Wu, Jiajing; Dong, Li; Liu, Tiejun; Wang, Ziqi (Frontiers in Psychiatry, 2024)
Introduction: Subjective cognitive decline (SCD) and mild cognitive impairment (MCI) are stages 2 and 3, respectively, of the Alzheimer’s continuum. The Alzheimer’s Disease Assessment Scale-Cognitive Subscale (ADAS-cog’s) ten-words recall test is a validated method for the early detection of cognitive impairment in Alzheimer’s disease. However, limited studies have investigated its ability to differentiate between SCD and MCI. Methods: 203 participants with SCD and 62 participants with MCI underwent multiple neuropsychological assessments. The Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment-Basic (MOCA-B) served as brief global cognition tests. A binary logistic regression model was used to analyze the potential factors affecting MCI. The accuracy of the ten-words recall test was assessed using the area under the receiver operating characteristic (ROC) and the area under the curve (AUC). Results: The neuropsychological assessment revealed significant differences in the ten-words recall test scores between the SCD (median age 61 years; 70.44% female) and MCI (median age 64 years; 61.29% female) groups (p < 0.001), with the MCI group scoring the highest. Using a cut-off value of 3.15 for the ten-words recall test, sensitivity for distinguishing MCI from SCD reached 87%, while specificity stood at 61% (AUC 0.777, p < 0.001). DeLong’s test indicated no statistically significant difference in the ten-words recall test’s ability to distinguish between SCD and MCI compared to the total score of ADAS-Cog (AUC 0.833, p) and MMSE (AUC 0.784, p > 0.05). However, a significant difference was observed when compared to MoCA-B (AUC 0.973, p < 0.001). In the population with an education level of ≤ 9 years, the optimal cut-off value for the ten-words recall test was 3.15, yielding a sensitivity of 91% and a specificity of 45% (AUC = 0.674, p = 0.030). In the population with an education level > 9 years, the optimal cut-off value was 3.63, resulting in a sensitivity of 79% and a specificity of 71% (AUC = 0.785, p < 0.001). Discussion: The ten-words recall test from the ADAS-cog may detect MCI early owing to its simplicity and quick administration. It is an effective and convenient tool for rapidly identifying mild cognitive impairment.